Pendampingan UMKM dalam Era Digital: Studi Kasus Transformasi Domikids di Tengah Dinamika Persaingan Pakaian Anak - Tarihoran, Youngki Barani; Cristie, Anastasya Intan; Noviandri, Mohamas Arief (Fakultas Ekonomi & Bisnis Universitas Jenderal Soedirman, 2025)
This study focuses on assisting Domikids, a small-medium enterprise (SME) in the children's apparel sector, to overcome challenges in digital transformation amidst intense e-commerce competition. Domikids faced significant revenue declines due to inefficient digital marketing strategies and high operational costs. The assistance program implemented strategies to improve financial management, operational efficiency, and marketing performance. Financial interventions included structured accounting and cash flow monitoring. Operational optimization involved task distribution and performance-based incentives. Marketing strategies emphasized e-commerce optimization, social media expansion, and collaborations with local influencers. The results showed a 25% increase in sales on Shopee and improved brand visibility. These findings highlight the importance of digital transformation for SMEs in achieving business growth and competitiveness. This research serves as a practical guide for similar enterprises seeking to adapt and thrive in the digital era.